Towards an Australian model of culturally nourishing schooling. Issue 4 (4th July 2021) - Lowe, Kevin; Skrebneva, Iliana; Burgess, Cathie; Harrison, Neil; Vass, Greg
ABSTRACT: 2020 looms large for Indigenous education in Australia, with the 'Refreshed' Close the Gap strategy hanging over the collective heads of schools, Indigenous students and their families. After a decade of promises, there is now an acknowledgement within the government that programmes to improve student outcomes in literacy, numeracy and school engagement, as currently implemented, have little possibility in affecting the changes required to sustainably shift Indigenous student's schooling success. This paper draws together the findings from eleven concurrent systematic reviews of Australian Indigenous education (AER, 2019, 29(1)) and an in-depth analysis of four key underpinning elements of a culturally nourishing education for Australian Indigenous students. It is argued that the four tenets of this model centres on the curriculum construct of Learning from Country, the authentic inclusion of cultural practices and Indigenous languages in both curriculum and school practice, establishing epistemic and pedagogic mentoring for teachers and the development of a robust professional development model to support a transformative shift in teachers' pedagogic practices. The authors argue that a whole-school approach explicitly negotiated with and supported by Indigenous families, and that centres these key principles are required if the promise of educational success is ever to be met.